Governance in mitigating the effect of oil wealth on wealth inequality: A cross-country analysis of policy thresholds - Henri Njangang Ndieupa; Simplice Asongu; Sosson Tadadjeu; Yann Nounamo; Brice Kamguia (African Governance and Development Institute (AGDI), 2021)
The study assesses the role of governance in modulating the effect of oil wealth on wealth inequality in 45 countries in the world. The empirical evidence is based on Pooled Ordinary Least Squares and the Generalised Method of Moments. The findings show that oil rents unconditionally increase wealth inequality while govenance dyanmics (in terms of rule of law, corruption-control, government effectiveness, regulatory quality) moderate oil rents for an overall net negative effect on wealth inequality. Good governance thresholds at which the unconditional effect of oil rents on the wealth inequality changes from positive to negative are computed and discussed. It follows that while governance is a necessary condition for improving the redistributive effects of oil wealth, it becomes a sufficient condition for net positive improvements in wealth distribution only when some critical levels of good governance have been reached. Other policy implications are discussed.
Keywords: F21; F54; L71; 330; Governance; Oil wealth; Wealth inequality; Panel data